Implementation of Distance and Digital Learning During Pandemic Covid-19 in Malaysia - Ismail, Affero; Ahmad Syakir, Afham Haziq; Bahrudin, Ida Aryanie; Samsudin, Noor Azah; Mohamed Shafieek, Muhammad Shahrir (Online Journal for TVET Practitioners, 2022)
Due to physical constraints preventing Covid-19 spread, TVET institutions are unable to develop and offer their courses effectively. Almost every country in the world has been affected by the pandemic Covid-19. Many students are having difficulty, limiting their access to a high-quality education. This scenario shines a light on how stakeholders can guarantee that the curriculum continues to operate even if students are unable to attend school. Many initiatives have been conducted, including curricular innovation and digitalization. The learning materials are transformed to digital form, and the curriculum delivery is done online. This involves the use of Open Educational Resources (OER). Many institutions are also implementing cutting-edge technology, such as Augmented Reality (AR) and Virtual Reality (VR), to improve studentâ€™s learning. However, challenges and issues occurred in terms of institutions’ preparation to transition from traditional learning, and students’ readiness in terms of physical equipment and connectivity. This article will discuss the strategies and initiatives taken by the Malaysian Government and the TVET institutions to deliver quality education including the issues and challenges that most TVET institutions confront particularly the teachers and lecturers. The findings of this article elaborate the best practices initiated during pandemic. Furthermore, based on the online survey, the studentâ€™s perception on distance learning is at moderate level with mean=2.875, SD=0.95. The outcome of this paper may be used as a guideline in the development and planning of TVET curriculum and delivery.